Islamic Republic of Iran : Power Sector Note - World Bank (Washington, DC, 2014)
Over the past decade, the Iranian electricity sector's ability to supply reliable service has come under increasing pressure. This is evidenced by more frequent gas supply constraints to generation plants, high levels of debt and increasing losses in the network. The key roots of the problems in the sector are the under-pricing of natural gas which fuels the majority of the power generation, and the low retail electricity tariffs which lead to high per capita consumption of electricity and thus large investment requirements in new generation capacity to keep up with the demand. The Government of Iran is aware of the challenges and is pursuing a number of reforms to improve the performance of the sector, including private sector participation in the generation of electricity and implementation of a power pool with a view of developing a competitive market. While these reforms will eventually contribute towards a more sustainable sector, their implementation and success will require tackling the under-pricing of natural gas and electricity. Without tackling these issues, the impact of reform efforts will remain limited and to some extent academic, and run the risk of increasing the Government's fiscal exposure as under-writer of the policies and transactions in the sector. This Note reviews some key challenges in the sector and highlights their strategic implications. The Note also provides some suggested next steps in the form of a "road-map" to address these issues.